64: Epidemiology and Determinants of Transfusions of Red Blood Cells, Plasma and Platelet Concentrates in a Neonatal Intensive Care Unit (NICU): A Single Center Cohort Study. Issue 6 (1st June 2014) - Villeneuve, A; Lapointe, A; Lachance, C; Ducruet, T; Lacroix, J
Abstract: BACKGROUND: Blood product transfusions are common in NICU, but transfusion practices are not well described. OBJECTIVES: To describe the incidence and determinants of red blood cells (RBC), plasma and platelets transfusions in our NICU. DESIGN/METHODS: Single-center prospective observational cohort study. All neonates admitted to the NICU of CHU Sainte-Justine Hospital (level 3B) from May 30 to August 6 2013 were included. Daily data were extracted from medical charts using a validated case report form up to 44 weeks post conception or discharge. Clinician's justifications for transfusion were assessed using a questionnaire. RESULTS: All 152 patients admitted in the NICU during the study period were included. Mean (± SD) birth weight (BW) and gestational age (GA) were 2.41±1 kg and 34.4±4.3 weeks. At least one RBC, plasma or/and platelets transfusion was given in 19 (12.5%) patients. RBC, plasma and platelets were transfused to 16 (10.5%), seven (4.6%) and seven (4.6%) patients respectively. Six (37.5%) of the RBC, three (43%) of the plasma and four (57%) of the platelets transfused patients received single transfusion. Donor exposure was restricted to only one in 14 (87%) of RBC, in four (57%) of plasma and in five (71%) of platelets recipients. Compared to non transfused patients, those who received at least one blood product transfusion had a significantly lower platelets level on the cord sample (172×10 9 /L vs 236×10 9 /L; P=0.01). Sex, GA, BW, cord hemoglobin (Hb) were comparable among both groups. Transfused patients were more frequently admitted for suspected bacterial infection (P=0.01) and hypoxic-ischemic encephalopathy (HIE) (P<0.001). At admission, neonates with higher SNAPPE-II score (P<0.001), on high frequency ventilation (HFV) (P<0.001) and with lower Hb (138 g/L vs 175 g/L; P<0.001) were more likely to receive transfusion during their NICU stay. Most frequently quoted justifications for RBC transfusions were repectively 1 – low Hb level, 2 – intent to improve oxygen delivery and 3 – severity of the illness. CONCLUSIONS: In this study, transfusions were not as frequent as expected. Lower platelets count on the cord sample and admission for bacterial infection or HIE are associated with transfusions in NICU patients. A higher SNAPPE-II score, HFV and lower Hb at admission in NICU are significant determinants for later RBC, plasma and/or platelets transfusions.